Foreign Labor Migration: Causes and Educational Impact - Upadhyaya, Ashok Bhakta (Sahayaatra सहयात्रा, 2022)
Foreign labour migration has been a common source of discourse along with socio-economic consequences on the place of local, federal, state, region and the world. It has brought impacts on different aspects of life including education. So, this study examines the causes of foreign labour migration and its educational impact on the households of Chhewetar, Gorkha. The study followed the quantitative method and survey design. The participants were selected by using systematic random sampling procedures. The questionnaire was used as the tool for data collection. The data were analyzed and interpreted by using descriptive statistics. The findings indicate that lack of employment, the poverty of the family and the wish of improving the economic status of a household were the major factors causing foreign employment. However, foreign employment has a positive impact on the educational status of the households because it improved the schooling of their children and enhances literacy levels. The income from foreign employment supported them in educating the children in urban areas, purchasing educational materials and paying tuition fees. The study concludes that foreign employment has been a boon in improving the educational status of foreign-employment migrant children.